Performance and physiological changes in highly trained swimmers during altitude training - Pyne, D. (Coaching & Sport Science Journal, 1998)
This article does not provide evidence that supports the benefit of altitude training camps other than to show that training at altitude improves altitude performances. It does not provide evidence that altitude training improves sea level performances in elite swimmers.